Are online learners frustrated with collaborative learning experiences? - Neus Capdeferro (Athabasca University Press, 2012)
Online education increasingly puts emphasis on collaborative learning methods. Despite the pedagogical advantages of collaborative learning, online learners can perceive collaborative learning activities as frustrating experiences. The purpose of this study was to characterize the feelings of frustration as a negative emotion among online learners engaged in online computer-supported collaborative learning (CSCL) experiences and, moreover, to identify the sources to which the learners attribute their frustration. With this aim, a questionnaire was designed to obtain data from a sample of online learners participating in the Master of ICT and Education program of the Universitat Oberta de Catalunya (UOC). Results revealed that frustration is a common feeling among students involved in online collaborative learning experiences. The perception of an asymmetric collaboration among the teammates was identified by the students as the most important source of frustration. Online learners also identified difficulties related to group organization, the lack of shared goals among the team members, the imbalance in the level of commitment and quality of the individual contributions, the excess time spent on the online CSCL tasks, the imbalance between the individual and collective grades, and difficulties in communication, among other factors leading to frustration. The analysis of the students’ sources of frustration in online CSCL is followed by a list of recommendations to the distance education stakeholders, aiming to reduce students’ frustration and improve the quality of their experiences in online CSCL contexts such as the UOC.